Effects of Fenugreek (Trigonella foenum-graecum L.) seed powder, as a feed supplement, on broiler carcass and meat characteristics - Abdalla, Isam; Ahmed, Jehan; Ali, Sayda (Gezira Journal of Agricultural Science; Vol 16 No 2 (2018), 2018)
The use of natural products in herbs to improve the efficiency of feed utilization and meat quality is important than antibiotics. The objectives of this study were to assess the effect of supplementation fenugreek seed powder on processed broiler chicken meat and carcass characteristics. A total of hundred and eight day-old male broiler chicks (Ross 308) were used at Elbashair farm in Wad Medani, Sudan. Chicks were randomly assigned in a completely randomized design into three groups (A, B and C) with three replicates. The experimental diets (starter and finisher) were formulated to satisfy the nutritional requirements of broiler chicks. The control birds (C) were fed a balanced broiler starter diet ad lib. Group (A) was fed basal diets supplemented with fenugreek seed powder (FSP) at1% ad lib in the first three days weekly for two weeks. Group (B) was fed basal diets supplemented with FSP at 1 % ad lib for the first 3 days through the entire period of the experiment (6weeks). At the end of the experiment, the birds live body weights were recorded and body weight gain was calculated. Two birds from each replicate were slaughtered, chilled and then weighed. Carcass weight, breast, thigh, deboned breast and deboned thigh weights were taken.Taste, flavor, tenderness, number of chewings and juiciness were determined using a taste panel. The results revealed that birds fed on 1% FSP recorded no significant differences in body weight gain compared to groups fed on control diet. Treatments had no significant effects on breast and thigh weight. Moreover , there were no significant effects on breast and thigh bones. Broiler fed FSP had no significant differences in tenderness, juiciness, flavor and taste and number of chewings of thigh meat. Also, no significant differences were found in breast meat tenderness, flavor and taste. There were significant differences in juiciness and highly significant differences in number of chewings. There were no significant difference in moisture content but there were significant difference in ash and highly significant differences in fat and protein. The study recommended using 1% fenugreek seed powder for improving brioler carcass weight and meat quality.     استخدام المنتجات الطبيعية كالأعشاب لتحسين الكفاءة الغذائية وجودة اللحوم أكثر إيجابية من المضادات الحيوية. هدفت هذه الدراسة الى تقييم أثر مسحوق بذور الحلبة )1%( على لحوم الفراخ المصنعة وبعض صفات الذبيح استخدمت 108 كتكوت ذكور عمر یوم من سلالة روس 308 بمزرعة البشاير. قسمت الكتاكیت عشوائیا إلي ثلاثة مجاميعِ A,B,C)) بثلاثة تكرارات. ركبت عليقة التجربة (بادي ونهاي) لتفي الاحتياجات الغذائية للدجاج اللاحم. الطيور القياسية (C) غذيت بعليقه بادئة متوازنة. المجموعة (A) عليقه قياسية مضافة إليها مسحوق بذور الحلبة في الثلاث أيام الأولى أسبوعياً  لمدة أسبوعين. المجموعة (B) غذيت على العليقة القياسية (بادي ونهاي) مضافة إليها مسحوق بذور الحلبة في الثلاثة أيام الأولى في عمر أسبوعين حتى نهاية التجربة في ستة أسابيع. ثم في نهاية التجربة سجل وزن الجسم الحي وثم حسب الوزن المكتسب ومن تم ذبح اثنين طائر من كل تكرار ووزنت الفراخ في حالة جامدة. اخذ وزن الجسم والصدر والفخذ ولحم الصدر ولحم الفخذ لاختبار صفات الجودة  التذوق والنكهة والطراوة وعدد المضغات والعصيرية. أوضحت النتائج أن الدجاج الذي تم تغذيته على مسحوق الحلبة انه لا توجد فروقات معنوية في وزن الجسم المكتسب لكل المجموعات التي تغذت على الحلبة وأشارت النتائج أيضاً إلى عدم وجود فروقات معنوية بين لحم الصدر ولحم الفخذ في أوزانهم. وأيضاً لا توجد فروقات معنويةً بين عظمة الصدر وعظم الفخذ وأشارت النتائج أيضا أن لحم الفخذ للفراخ التى غذىت على مسحوق الحلبة أنه لا توجد فروقات معنوية بين الصفات الطراوة والعصيرية والنكهة والطعم وعدد المضغات بالنسبة للحوم الصدور. لا توجد فروقات معنوية  بين الصفات الطراوة والنكهة والطعم ولكن توجد فروقات معنويةً  (P>0.05) في العصيرية وفروقات عالية(P<0.01)  في عدد المضغات. في التحليل الكيميائي لم تكن هناك فروقات معنوية (P>0.05) في الرطوبة، ولكن كانت هناك فروقات معنوية (P>0.05) في الرماد وتوجد فروقات معنوية عالية (P<0.01) في الدهن والبروتين. ومن نتائج البحث توصي الدراسة بان يتم استخدام نسبة 1% من مسحوق بذور الحلبة لتحسين الوزن وبعض صفات اللحم.